Ethical issues identified in nurses´ interprofessional collaboration in clinical practice: a meta-synthesis - Pakkanen Piiku; Haggman-Laitila Arja; Kangasniemi Mari (Taylor & Francis Inc, 2022)
The aim of this study was to synthesize previous knowledge about ethics in nurses' interprofessional collaboration in clinical practice. Although healthcare professionals have common goals and shared values, ethical conflicts still arise during patient care. We carried out a meta-synthesis of peer-reviewed papers published in any language from 2013-2019, using both electronic searches, with the CINAHL, PubMed, Scopus, and SocINDEX databases, and manual searches. We identified 4,763 papers and selected six qualitative papers, and three theoretical papers, based on predetermined inclusion and exclusion criteria and quality appraisal. The studies came from the USA, Canada, Sweden, Australia, Botswana, and the Netherlands. We found that in ethics studies on nurses' interprofessional collaboration in clinical practice the focus has been on factors that affect how patients receive care. These factors were patients' wishes, whether they were told the truth about their condition, and how different professionals recognized and treated their pain. The focus in the papers we reviewed was on the roles of different professionals during the care process, including ethical conflicts with regard to their aims, commitment, and the balance of power among them and other professions. More research is needed to raise the visibility of how nurses and other professionals recognize, and evaluate, their professional and interprofessional ethics.